Exploring the fundamentals of Ni-based superalloy single crystal (SX) alloy design: Chemical composition vs. microstructure - Horst, O. M.; Adler, D.; Git, Paul; Wang, H.; Streitberger, J.; Holtkamp, M.; Jöns, N.; Singer, Robert; Körner, Carolin; Eggeler, G. (Materials & Design, 2020)
The present work contributes to a better understanding of the basic assumptions and principles behind the design of Ni-based single crystal superalloys (SXs). For this purpose, we cast and heat-treat four Ni-based single crystal superalloys (SXs) and compare their creep performances: ERBO/1 (with Re) and three ERBO/15 variants (no Re but increased levels of Ti, Mo and W). We show that Re can be replaced by other elements without losing creep strength. To come to this conclusion one has to consider both, alloy composition and microstructure. We analyze the mechanical, microstructural and chemical results (creep rates, γʼ-volume fractions, average γʼ-particle sizes, average γ-channel widths and the chemistry of γ- and γʼ-phases) obtained for ERBO/15 and its two leaner variants (less Mo: ERBO/15-Mo and less W: ERBO/15-W). ERBO/15-Mo and ERBO/15-W show higher creep rates than ERBO/15, because they exhibit lower Mo and W concentrations in the γ-channels. This results in higher diffusion rates, accelerated rafting and faster dislocation climb at γ/γʼ-interfaces.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Creep rate; Effects of Re; Ti; Mo and W; Heat treatment; Local alloy composition; Microstructure; Ni-based single crystal superalloys (SX)